Sex differences in exercise metabolism and the role of 17-beta estradiol - Tarnopolsky, M. A. (Medicine & Science in Sports & Exercise, 2008)
Women oxidize more lipid and less carbohydrate and protein compared with men during endurance exercise. The increase in fat oxidation is associated with higher intramyocellular lipid content and use as well as greater adipocyte lipolysis. Glucose rates of appearance and disappearance are lower for women than for men, with no change in basal muscle glycogen, and some evidence for muscle glycogen sparing during endurance exercise. Women oxidize less protein compared with men and show lower leucine oxidation during exercise. The consistent and robust finding of higher mRNA abundance for most components of fat-oxidation pathways in women compared with men is directionally consistent with the substrate-oxidation data. A lack of directional consistency between mRNA species involved in carbohydrate and protein metabolism and the known sex differences during exercise implies that fat oxidation is regulated and that carbohydrate and protein oxidation follow by metabolic demand. Administration of 17-beta-estradiol to men recapitulates most of the described sex differences in metabolism and mRNA content. The greater fat oxidation for women during submaximal endurance exercise compared with men seems to occur partly through a sex hormone-mediated enhancement of lipid-oxidation pathways.